Culture of Safety Practices in Patient Care at Dr. Lorenzo P. Ziga Memorial District Hospital - Cestina, Joanna Marie; Alcala, Emerlinda (International Journal of Sustainability and Advanced Integrated Research, 2026)
District hospitals like Dr. Lorenzo P. Ziga Memorial District Hospital face unique challenges in maintaining patient safety amid resource constraints and variable staffing, making a strong safety culture essential for preventing adverse events and promoting accountability. This descriptive quantitative study assessed nurses' perceptions of safety practices using Donabedian's Structure-Process-Outcome model and High Reliability Organization theory, surveying 50 nurses via total population sampling with a validated questionnaire featuring Likert-scale and Yes/No items analyzed through frequencies, percentages, and weighted means. Findings revealed a young, contractual workforce (predominantly 20-30 years old,
Keywords: Safety culture; Patient safety; Error reporting; Communication practices; High Reliability Organization; Philippines